2023
DOI: 10.2174/1574893618666230227103427
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Biomarkers in Stomach Adenocarcinoma using Machine Learning Approaches

Abstract: Background: Stomach adenocarcinoma (STAD) is common cancer with poor clinical outcomes globally. Due to a lack of early diagnostic markers of disease, the majority of patients are diagnosed at an advanced stage. Objective: The aim of the present study is to provide some new insights into the available biomarkers for patients with STAD using bioinformatics. Methods: RNA-Sequencing and other relevant data of patients with STAD from The Cancer Genome Atlas (TCGA) database were evaluated to identify differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In addition, the importance of miRNA-mRNA networks in activating or inhibiting many cancer-related molecular signaling pathways has recently been observed 31 , 32 . Recently, with the development of bioinformatics as well as the aid of machine learning algorithms, different forms of next-generation sequencing are increasingly being used to detect biomarkers with a role in early detection, treatment, and prognosis of cancer 33 35 . Machine learning approaches have gained popularity due to their predictive power of diagnostic and prognostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the importance of miRNA-mRNA networks in activating or inhibiting many cancer-related molecular signaling pathways has recently been observed 31 , 32 . Recently, with the development of bioinformatics as well as the aid of machine learning algorithms, different forms of next-generation sequencing are increasingly being used to detect biomarkers with a role in early detection, treatment, and prognosis of cancer 33 35 . Machine learning approaches have gained popularity due to their predictive power of diagnostic and prognostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies identified prognostic and diagnostic biomarkers in colorectal cancer and gastric cancer using RNA-seq analysis and machine learning [17][18][19]. In contrast to our previous study, the current study was designed based on an integrated two omics and deep learning approach to identify prognostic and diagnostic biomarkers in colorectal cancer (CRC) patients at different disease stages (early and metastatic).…”
Section: Discussionmentioning
confidence: 99%
“…TCGA (Cancer Genome Atlas), an integrated collection of clinical information and gene sequencing data, allows systematic analysis of the molecular mechanisms underlying clinical features associated with cancers, for example. It contributed to improved diagnostic methods and ultimately improved the survival prognosis of cancer patients by assessing the pathological stage, histological type, tumor grade, diagnosis, and prognosis of the disease (19)(20)(21)(22). This study used the TCGA database for gene expression proo ng and machine learning to identify differential expression genes (DEGs) of PRCC tumors.…”
Section: Introductionmentioning
confidence: 99%